Analysis of Water Quality Habitat for Cempedik Fish (Osteochilus spilurus) in Different Waters on Bangka Island - Mahendra, Nadhiva; Saputra, Farhan Afif; Santoso, Agus Budi; Anjani, Tiara Puspa; Kurniawan, Ardiansyah (Universitas Cokroaminoto Palopo, 2024)
Abstract Water quality is one of the important parameters in the life of cempedik fish. The research aims to examine the characteristics of water quality in different rivers. This research was carried out using a purposive sampling method, namely sampling in three different locations. The research locations are the Jade Bahrin River (Bangka), the Tugang River (West Bangka), and the Bencah River (South Bangka). The parameters taken in this research are physical parameters and chemical parameters. The results of this research are sandy mud river substrate with clear to brown water color, water temperature 27 ºC -28 ºC; Water pH 4 -6; Dissolved oxygen 3 – 5 mg/l. The aquatic plants around the cempedik fish habitat are Cryptocoryne, Scirpodendron ghaeri, Pallavicinia lyllii, Pandanus, Eleocharis montevidensis, Salvinia, Nipah, and Bladderworts Keywords: Water Quality, Cempedik Fish, Bangka Island